Contribution of Insurance Business In Nepal - Kharel, Khom Raj (Economic Journal of Nepal, 2019)
This study aims to find the contribution of insurance business in Nepalese economy. The insurance sector is assumed to be an infrastructural pillar of the financial sector of the economy. The role of insurance business has been growing importance in financial intermediation, which has received less attention than bank and stock markets. The ultimate goal of insurance business is to provide security to insurance industry according to national need by protecting all classes of the society from natural and social risks while embracing the globally accepted insurance norms. There has been significant contribution of insurance business boosting economic development of Nepal. The objective of the study is to investigate insurance business and examine its contribution on financial resources mobilizations in Nepal. For this theoretical analysis, different research studies have studied to draw the fundamental issues of insurance business in the economy. The simple statistical tools have been applied to analyze the collected data. Furthermore the findings of the study emphasize the development of insurance business and its contribution in mobilizing financial resources needs to be paid more attention in financial sector analysis and macroeconomic policy.